8q24/MYC rearrangement is a recurrent cytogenetic abnormality in blastic plasmacytoid dendritic cell neoplasms. (March 2018) - Boddu, Prajwal C.; Wang, Sa A.; Pemmaraju, Naveen; Tang, Zhenya; Hu, Shimin; Li, Shaoying; Xu, Jie; Medeiros, L. Jeffrey; Tang, Guilin
Highlights: About 10–15% patients with BPDCN harbor 8q24/ MYC rearrangement. MYC often partners with a non-immunoglobulin gene in BPDCN. MYC rearrangement does not convey a more aggressive clinical course in BPDCN. BPDCN with MYC rearrangement often response well to ALL-based chemotherapy. Abstract: 8q24 /MYC rearrangements resulting in MYC overexpression occur most frequently in lymphoid neoplasms. MYC rearrangements rarely have been described in blastic plasmacytoid dendritic cell neoplasm (BPDCN). Over an 8-year period in our hospital, 5 of 41 (12%) patients with BPDCN were shown 8q24/ MYC rearrangements, including 2 with t(6;8)(p21;q24), 1 with t(8;14)(q24;q32), 1 with t(X;8)(q24;q24), and 1 with t(3;8)(p25;q24). 8q24/ MYC rearrangement was present in the stemline in 4 patients and in the sideline in one; the latter was a patient with primary myelofibrosis who then developed BPDCN. MYC overexpression by immunohistochemistry was variable, but largely correlated with the percentage of blasts. Four patients were treated with acute lymphoblastic leukemia-type chemotherapy regimens and 3 had a good response; 1 patient was treated with acute myeloid leukemia-type regimens and was refractory to therapy. By the end of the follow-up, 3 patients died and 2 were alive in complete remission. We conclude that 8q24/ MYC rearrangements occur in 10–15% of BPDCN, often partnered with non-immunoglobulin chromosomal loci, and may play a role in BPDCN pathogenesis. In this small patient sample, patients with BPDCN and MYC rearrangement often responded to therapy with acute lymphoblastic leukemia-type chemotherapy regimens.